2002
DOI: 10.1256/003590002320603584
|View full text |Cite
|
Sign up to set email alerts
|

Areas beneath the relative operating characteristics (ROC) and relative operating levels (ROL) curves: Statistical significance and interpretation

Abstract: SUMMARYThe areas beneath the relative (or receiver) operating characteristics (ROC) and relative operating levels (ROL) curves can be used as summary measures of forecast quality, but statistical signi cance tests for these areas are conducted infrequently in the atmospheric sciences. A development of signal-detection theory, the ROC curve has been widely applied in the medical and psychology elds where signi cance tests and relationships to other common statistical methods have been established and described.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
527
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 734 publications
(531 citation statements)
references
References 88 publications
3
527
0
1
Order By: Relevance
“…In fact, the AUC metric has been shown to be equal to the probability of, given a pair of items with different labels (one "success" case and one "failure" case, in our situation), correctly considering the item that was truly a "success" as more likely to be a "success" case than the other item. It has also been shown to be related to other important statistical metrics, such as the Wilcoxon test of ranks, the Mann-Whitney U and the Gini coefficient [32,33,59].…”
Section: Multiple Threshold Analysismentioning
confidence: 99%
“…In fact, the AUC metric has been shown to be equal to the probability of, given a pair of items with different labels (one "success" case and one "failure" case, in our situation), correctly considering the item that was truly a "success" as more likely to be a "success" case than the other item. It has also been shown to be related to other important statistical metrics, such as the Wilcoxon test of ranks, the Mann-Whitney U and the Gini coefficient [32,33,59].…”
Section: Multiple Threshold Analysismentioning
confidence: 99%
“…In order to estimate the statistical significance of each k-ellipse, we have to resort to the statistics of the Area Under the Curve (AUC), labelled by A, in the ROC plane which has been the subject of the study by Mason and Graham [10]. Mason and Graham [10] have shown that…”
Section: The K-ellipses Familymentioning
confidence: 99%
“…For large values of P and Q, i.e., when P or Q are greater or equal to 30 and P + Q ≥ 40, the U-statistics can be [10] approximated by a Gaussian distribution having a mean…”
Section: The K-ellipses Familymentioning
confidence: 99%
See 1 more Smart Citation
“…MOS applied to 42 years of DEMETER (Palmer et al, 2004) data, and in particular DJF forecast fields produced by the UKMO fully coupled system, show correlation skill patterns over South Africa (not shown) similar to the ECHAM4.5-MOS simulations presented here. In addition to the similarities in the spatial distribution of the correlation fields, additional verification parameters such as linear error in probability space (LEPS) (Potts et al, 1996) and relative operating characteristic (ROC) scores (Mason and Graham, 2002) show patterns similar to the correlation fields (not shown). Therefore, as stated earlier, the correlation maps presented here should be considered good approximations of model performance spatially.…”
Section: Simulation Skill Levels For the 10-year Periodmentioning
confidence: 99%